EFEKTIVITAS APLIKASI JENIS PUPUK ORGANIK CAIR DAN BIOCHAR TERHADAP PRODUKSI TANAMAN SAWI PAKCOY (Brassica rapa L.) - Emmy Hamidah; Istiqomah Istiqomah; Ela Nur Fadhillah (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
As Indonesia's population increases, pak choy mustard greens (Brassica rapa L.) are increasingly popular with the general public. However, this increase in demand is not accompanied by an even increase in supply. The use of biochar and liquid organic fertilizer is considered to be able to overcome this problem in order to increase the production of pak choy mustard greens. The aim of this research was to determine the effect of using biochar and liquid organic fertilizer on the growth of pakcoy mustard greens. This research was carried out from March to May 2023 in German Village, Sugio, Lamongan. This research uses a Factorial Randomized group Design Method (RAKF) which involves two factors with three levels of each factor. Which consists of types of liquid organic fertilizer: cow biourine, rabbit biourine, Poc Nasa as well as biochar type factors: rice husk biochar, corn cob biochar, coconut shell biochar. Fisher's test (F test) was used to perform an analysis of variance on the data collected from these observations, with a significance level of 5% and 1%. The Least Significant Difference test was applied at the 5% significance level to further analyze the treatment that had a significant impact. In particular, the parameters of plant height and number of leaves at the age of 14 days after planting showed significant variations between the various biochar treatments, based on the results of the analysis of variance. Interactions between these factors were also recorded. Fresh weight per plant, wet weight per plot and wet weight per hectare, as well as plant height and number of leaves at 21, 28 and 35 days after planting. In particular, the use of treatments involving rabbit biourin and corncob biochar gave the best results in this investigation.